FUZZY SIMPLE ADDITIVE WEIGHTING PENENTUAN SMARTPHONE PENUNJANG BELAJAR MAHASISWA STMIK PRINGSEWU - Hafidin, Hasan (Bappeda Kabupaten Pringsewu, 2018)
The level of development of the use of information technology in Indonesia increasingly sophisticated and can not be avoided. The increasing age, the smartphone comes with a high specification and prices that are accessible to the public in Indonesia. So the lack of information about the smartphone specifications greatly influence the selection of smartphones used. Based on these problems, he built a Decision Support System for selecting a smartphone that fits the needs of consumers. The system is built using Simple Additive Weight (SAW). by providing criteria that meet the needs of smartphone namely (1) ram (2) storage memory (3) the size of the screen (4) the capacity of the battery (5) camera (6) network. Then the alternative that has the highest score is 3 v3 to v4 with value 0.92 0.89 v5 value to the value of 0.82.